Anti-precipitation effects of TiO2 and TiOSO4 on positive electrolyte of vanadium redox battery - Gencten, Metin; Gursu, Hurmus; Sahin, Yucel (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, the effects of TiO2 and TiOSO4 on the precipitation of the positive electrolyte of vanadium redox battery (VRB) systems were investigated. TiO2 and TiOSO4 were used as anti -precipitating agents for V(V) ions at 40 and 60 degrees C. The optimum amounts and electrochemical properties of additives were determined by electrochemical methods such as cyclic voltammetry and electrochemical impedance spectroscopy. The optimum amount of additives was identified as wt% 0.004 and 0.003 for TiO2 and TiOSO4, respectively. The structural features and composition of electrodes were investigated by scanning electron microscopic and energy-dispersive X-ray analysis. A plausible reaction mechanism was also proposed for redox reaction occurring on the positive electrode of a VRB. The concentration of V(V) ions in the additive including electrolyte were higher than that of blank solution at the end of the thermal precipitation tests. According to thermal and electrochemical studies, TiO2 and TiOSO4 can be useful additives for the positive electrolyte of a VRB. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Vanadium redox battery; Additive; Cyclic voltammetry; Positive electrolyte; Anti-precipitation agents; RENEWABLE ENERGY SYSTEM; FLOW BATTERY; ELECTROCHEMICAL PROPERTIES; ORGANIC ADDITIVES; CELL ELECTROLYTE; STORAGE; ACID; MEMBRANE; Chemistry; Electrochemistry; Energy & Fuels